2021
DOI: 10.1016/j.trsl.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of highly expressed interferon-stimulated genes associate more with African ancestry than disease activity in patients with systemic lupus erythematosus. A systematic review of cross-sectional studies

Abstract: Type I interferons (IFN) are central players in the pathogenesis of systemic lupus erythematosus (SLE) and the up-regulation of interferon-stimulated genes (ISGs) in SLE patients is subjected to increasing scrutiny as for its use in diagnosis, stratification and monitoring of SLE patients. Determinants of this immunological phenomenon are yet to be fully charted. The purpose of this systematic review was to characterize expressions of ISGs in blood of SLE patients and to analyze if they associated with core de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 79 publications
3
12
0
Order By: Relevance
“…In AA, we noted no significant association between anti-dsDNA and the IGS, but a significant association with anti-RNP, whereas in EA SLE the association between the IGS and anti-RNP was significantly greater than that of anti-dsDNA and the IGS. This is consistent with a recent report noting an AA-specific IGS, characterised by greater enrichment in AA SLE patients than EA patients and enrichment occurring with lower frequency and magnitude in autoantibody-stratified EA than AA patients 41. It is notable that we found that this subset of the IGS was more frequent in AA SLE, but it appeared to be more related to the presence of anti-RNP antibodies, which were more common in AA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In AA, we noted no significant association between anti-dsDNA and the IGS, but a significant association with anti-RNP, whereas in EA SLE the association between the IGS and anti-RNP was significantly greater than that of anti-dsDNA and the IGS. This is consistent with a recent report noting an AA-specific IGS, characterised by greater enrichment in AA SLE patients than EA patients and enrichment occurring with lower frequency and magnitude in autoantibody-stratified EA than AA patients 41. It is notable that we found that this subset of the IGS was more frequent in AA SLE, but it appeared to be more related to the presence of anti-RNP antibodies, which were more common in AA.…”
Section: Discussionsupporting
confidence: 93%
“…The GSVA R package was used as a non-parametric, unsupervised gene set enrichment method 37. The inputs for the GSVA algorithm were log2 microarray expression values (Affymetrix Human Transcriptome Array V.2.0) and predefined gene sets describing IFN stimulated gene signatures,15 38–41 TNF38 and interleukin 1 (IL-1) cytokine signatures 15. Probes were filtered out if their IQR was equal to zero.…”
Section: Methodsmentioning
confidence: 99%
“…The present results are consistent with previous findings showing that elevated type I IFN stimulated genes and the development of lupus nephritis were the most prevalent in a population of SLE patients with African ancestry [ 28 ]. Jenks et al showed that there was a disproportionally higher number of African American SLE who developed active disease, nephritis, high anti-Smith, and anti-RNP autoAbs.…”
Section: Discussionsupporting
confidence: 93%
“…The basis for ancestral differences in IFN expression is not well-explained. A study shows that in SLE patients a cluster of highly expressed ISGs including IFI27 is more associated with African ancestry than disease activity ( 32 ). Our study which combines cohorts from ethnically diverse populations (Middle Eastern, Asian, European & South American) shows robust nature of IFI27 as a prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%